Does Inequality Matter for the Consumption-Wealth Channel? Empirical Evidence - Luc Arrondel; Pierre Lamarche; Frédérique Savignac (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies the heterogeneity of the marginal propensity to consume out of wealth based on French household surveys. This heterogeneity is driven by differences in both wealth composition and wealth levels. We find a decreasing marginal propensity to consume out of wealth across the wealth distribution for all net wealth components. The marginal propensity to consume out of financial assets tends to be higher compared with the effect of housing assets, except at the top of the wealth distribution. The marginal propensity to consume out of housing wealth increases with debt pressure and depends on debt composition. Based on a simulation exercise, we find a limited effect of wealth shocks on consumption inequality. An increase in stock prices tends however to slightly increase consumption inequality, especially at the top of the distribution.
Keywords: D12; E21; C21; 330; consumption; marginal propensity to consume out of wealth; policy distributive effects; household survey